First aid video development to overcome excessive anxiety and fear as physically, psychologically, and spiritually - Gregorius Editya Koes Pradana Putra; Anastasya Marsella Putri; Feronika Hulu; Mektilde Noni (Indonesian Institute for Counseling, Education, and Therapy (IICET), 2022)
First aid is one of the assistance provided to victims of accidents, both traffic accidents and natural disasters. We all know that Indonesia is a country that cannot be separated from natural disasters and disasters every year. Accidents are unplanned actions and cannot be controlled by anyone. Therefore, it is important to provide understanding to the public about first aid techniques so that they can provide assistance to people who experience accidents and traffic accidents without waiting for medical personnel. Saving the souls of others is a noble behavior and the slightest help we give to others who are in dire need we do it for God Himself. Everyone who experiences a traffic accident or natural disaster must have an impact on the victim, both physically and psychologically. Physical impacts such as injuries to the body, broken bones, pain in the body, and scars. Psychological impacts such as stress, depression, anxiety, trauma, and excessive fear. This article presents how to deal with excessive anxiety and fear physically, psychologically, and spiritually.